ANALISIS IMPLEMENTASI KURIKULUM MERDEKA (IKM) DALAM MENINGKATKAN MINAT BELAJAR SISWA DI SMA NEGERI 1 BINJAI KABUPATEN LANGKAT TAHUN AJARAN 2024-2025 - Jelly litiana br. Pinem; Hamidah Darma; Lendra Fahrurrowzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze how the implementation of the Merdeka Curriculum can increase students' interest in learning at SMA Negeri 1 Binjai, Langkat Regency, in the 2024–2025 Academic Year. This research is descriptive with a qualitative approach. The data collection instrument used was an in-depth interview guide. The research subjects consisted of the principal, the deputy principal for curriculum, two subject teachers, and two students who are members of the Student Council (OSIS). The results showed that the Merdeka Curriculum was able to increase students' interest in learning through flexible, participatory, and relevant learning that caters to students' needs. Teachers play an important role as facilitators and innovators in supporting student-centered learning. Nevertheless, challenges were still encountered, especially concerning teacher readiness, limitations in facilities and infrastructure, and student adaptation to active learning methods.